TLR2 Promotes Monocyte/Macrophage Recruitment Into the Liver and Microabscess Formation to Limit the Spread of Listeria Monocytogenes - Wang, Guan; Zhao, Huajun; Zheng, Bingqing; Li, Dongxuan; Yuan, Yi; Han, Qiuju; Tian, Zhigang; Zhang, Jian (Frontiers in Immunology, 2019)
TLR2 signaling plays a critical protective role against acute Listeria monocytogenes (Lm) infection by up-regulating inflammatory cytokines and promoting macrophage antimicrobial capabilities. However, the underlying mechanism by which TLR2 regulates hepatic macrophage-mediated anti-Lm immune responses remains poorly understood. In this study, we found that both the absolute number and proportion of monocyte/macrophage (Mo/MΦ) in the liver and spleen of Tlr2-/- mice were significantly lower compared to wild type mice. Changes in TLR2 signaling in both hepatocytes and Mo/MΦs were associated with the infiltration of Mo/MΦs in response to Lm-infection. Analyses by proteome profiler array and ELISA revealed that hepatocytes recruited Mo/MΦs via TLR2-dependent secretion of CCL2 and CXCL1, which was confirmed by receptor blocking and exogenous chemokine administration. Importantly, we found that TLR2 contributed to macrophage mobility in the liver through a TLR2/NO/F-actin pathway, facilitating the formation of macrophage-associated hepatic microabscesses. Moreover, TLR2 activation induced the expression of several PRRs on hepatic macrophages associated with the recognition of Lm and augmented macrophage bacterial clearance activity. Our findings provide insight into the intrinsic mechanisms of TLR2-induced Mo/MΦ migration and mobility, as well as the interaction between macrophages and hepatocytes in resistance to Lm infection.